Pelaksanaan Perjanjian Kredit Dengan Jaminan Surat Ijin Mengguna Usahakan Tempat Dagangan Di Pasar ( Studi Kasus Di Pd.Bpr Djoko Tingkir Sragen ) - Nuryani, Siti; , Septarina Budiwati, S.H., M.H (2017)
This study aims to determine the implementation of the Credit Agreement with Guarantee Permit use you Keep the Merchandise in the Market Place, as well as to determine the settlement of loans with collateral permit use you try to place merchandise on the market if the Borrower defaults. The authors use method approach is an approach empirical juridical approach. Methods of data collection in this study using field studies and literature, which is done by collecting data in the field with the interview. Based on the results of research and discussion it can be concluded that the implementation of the credit agreement in PD. BPR Djoko Tingkir Sragen in accordance with the laws and regulations No. 10 of 1998 on the banks, but related to the use of collateral to permit use you try to place merchandise on the market do not have legal protection when used as collateral, while the settlement with the amicable way in which the Borrower is expected may sell the collateral to repay their debts. Keywords: Credit, Guarantees, Permit Trading.